Governed by digital technology?: Self-perpetuation and social domination in digital capitalism. (7th April 2023) - Klur, Konstantin; Nies, Sarah
Abstract : Digitalisation is often associated with the domination of technology over humans. This article aims to develop a concept of self-perpetuation that illuminates the relationship between technology and social domination instead of focusing only on technological properties. Drawing on Marx's concept of real subsumption and interviews in industrial companies, we analyse specific forms of self-perpetuation that take place in the digitalised working world. In doing so, we critically examine the diagnosis of digital Taylorism which assumes a comprehensive elimination of the subjectivity of workers. In contrast, we show that digital technology allows for other forms of domination based on the flexibility of living labour.